Low cost delivery of proteins bioencapsulated in plant cells to human non-immune or immune modulatory cells. (February 2016) - Xiao, Yuhong; Kwon, Kwang-Chul; Hoffman, Brad E.; Kamesh, Aditya; Jones, Noah T.; Herzog, Roland W.; Daniell, Henry
Abstract: Targeted oral delivery of GFP fused with a GM1 receptor binding protein (CTB) or human cell penetrating peptide (PTD) or dendritic cell peptide (DCpep) was investigated. Presence of GFP + intact plant cells between villi of ileum confirm their protection in the digestive system from acids/enzymes. Efficient delivery of GFP to gut-epithelial cells by PTD or CTB and to M cells by all these fusion tags confirm uptake of GFP in the small intestine. PTD fusion delivered GFP more efficiently to most tissues or organs than the other two tags. GFP was efficiently delivered to the liver by all fusion tags, likely through the gut–liver axis. In confocal imaging studies of human cell lines using purified GFP fused with different tags, GFP signal of DCpep-GFP was only detected within dendritic cells. PTD-GFP was only detected within kidney or pancreatic cells but not in immune modulatory cells (macrophages, dendritic, T, B, or mast cells). In contrast, CTB-GFP was detected in all tested cell types, confirming ubiquitous presence of GM1 receptors. Such low-cost oral delivery of protein drugs to sera, immune system or non-immune cells should dramatically lower their cost by elimination of prohibitively expensive fermentation, protein purification cold storage/transportation and increase patient compliance.